Birds and habitat relationships in changing landscapes - Fuller, Robert J. (Cambridge University Press, 2012)
The successful conservation of bird species relies upon our understanding of their habitat use and requirements. In the coming decades the importance of such knowledge will only grow as climate change, the development of new energy sources and the needs of a growing human population intensify the, already significant, pressure on the habitats that birds depend on. Drawing on valuable recent advances in our understanding of bird-habitat relationships, this book provides the first major review of avian habitat selection in over twenty years. It offers a synthesis of concepts, patterns and issues that will interest students, researchers and conservation practitioners. Spatial scales ranging from landscape to habitat patch are covered, and examples of responses to habitat change are examined. European landscapes are the main focus, but the book has far wider significance to similar habitats worldwide, with examples and relevant material also drawn from North America and Australia
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Ökologie; Birds / Habitat; Birds / Ecology; Birds / Effect of habitat modification on